2018
DOI: 10.1177/8756870518783522
|View full text |Cite
|
Sign up to set email alerts
|

Extending Caregiver Training Via Telecommunication for Rural Icelandic Children With Autism

Abstract: This study describes the development and evaluation of a behavioral parent training protocol via telecommunication for three parents of preschool children with autism, with limited access to behavioral expertise. A single-subject, multiple baseline experimental design across child behaviors, replicated across parents, was used to evaluate the effects of the training protocol. Dependent measures were collected via telecommunication for most assessments and included parent and child responses during naturalistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…However, it is important to consider that the purpose of the studies was not to focus on adaptations, per se, and that cultural adaptations are perhaps less likely to be reported when the entire research team is matched in language and ethnicity with the participants. The common use of interpreters and service providers matched in language and ethnicity lends further support to the recommendation of Fong and Tanaka (2013) to increase training and collaboration opportunities in behavior analysis for individuals from diverse cultures.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, it is important to consider that the purpose of the studies was not to focus on adaptations, per se, and that cultural adaptations are perhaps less likely to be reported when the entire research team is matched in language and ethnicity with the participants. The common use of interpreters and service providers matched in language and ethnicity lends further support to the recommendation of Fong and Tanaka (2013) to increase training and collaboration opportunities in behavior analysis for individuals from diverse cultures.…”
Section: Discussionmentioning
confidence: 75%
“…Translated Materials. Seven studies (Alnemary et al, 2015;Dai et al, 2018;Guðmundsdóttir et al, 2017;Guðmundsdóttir et al, 2018;Lee, 2015;Neely et al, 2020;Tsami et al, 2019) reported using translated materials either during the baseline phase or the training phase of the study. These studies used different methods for the translation process.…”
Section: Changes In Structure and Process Of Service Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies (18 studies, 81.8%) from our sample were conducted at least partially in homes. Access to technology and the necessary infrastructure can impose limitations to the advantages of telehealth (e.g., reliable Internet connection); however, successful implementation of telehealth intervention has been demonstrated in rural locations with families with less-than-optimal Internet connectivity [ 20 •].…”
Section: Introductionmentioning
confidence: 99%
“…There have been some great examples of behaviour analysts doing just that. By engaging in telehealth, families with children with autism are supported (Espinosa, 2020;Ferguson et al, 2019;Gundmundsdottir et al, 2019) and by ensuring adherence to recommended hygiene behaviours, such as washing or sanitising hands, contamination can be controlled, or even prevented (Bördlein, 2020;Walsh, 2020). Behaviour analysts have addressed issues related to stress, isolation, and mental health as well as learning of new skills (O'Donnell, 2019).…”
Section: Resultsmentioning
confidence: 99%